HUBUNGAN GAYA HIDUP DENGAN KEJADIAN HIPERTENSI DI RSUD LABUANG BAJI MAKASSAR - haikal alpin (Stikes Graha Edukasi Makassar, 2018)
Objective: The purpose of this study was to see the lifestyle relationship of hypertension occurrence at RSUD Labuang Baji Makassar. Method: In this study used the research design used in this study is cross sectional that researchers do observation or measurement of variables at one time. The sample size in this study are 30 respondents who match the inclusion criteria. The data were collected by using questionnaires. Results: The results showed that there was a correlation between smoking and hypertension (p = 0.029), there was a correlation between alcohol consumption and hypertension (p = 0.014), there was a relationship between high sodium consumption and hypertension (p = 0,002) the relationship between high fat consumption and the incidence of hypertension (p = 0.007), and there is a relationship between exercise with the incidence of hypertension (p = 0.001). Conclusion: The conclusion of this study is that there is a hubuangan between smoking, drinking alcohol, drinking alcohol consumption, high sodium consumption, and exercise with the incidence of hypertension. Suggestions: The results of this study can be used as a development of knowledge, especially about lifestyle relationships with the incidence of hypertension in the Inpatient Room Section of internal medicine in RSUD Labuang Baji Makassar